The global and regional burden and trends of migraine from 1990 to 2021: Global Burden of Disease Study 2021 - Lu, Ying; Li, Quan-yao; Gan, Lu; You, Yi; Wang, Chang-de; Guo, Zhao-wei; Shi, Jun; Liu, Xiao-ying (Frontiers in Neurology, 2025)
BackgroundMigraine is a common disabling neurological disorder that affects the quality of human daily life and mental health, potentially leading to disability and imposing a substantial disease burden. There is currently a lack of literature analysis on the global burden and changing trends of migraines. Therefore, this study is of great significance for the development of effective management and prevention strategies for migraine by analyzing the global burden of migraine and its changing trends.MethodsWe obtained data on the incidence, prevalence, and disability-adjusted life years (DALYs) of migraine by region and year from the Global Burden of Disease Study 2021 (GBD 2021). The estimated annual percentage change (EAPC) and 95% confidence interval (CI) were used to evaluate the time trend of disease burden, and factors that may affect the EAPC were analyzed. The burden of migraine was analyzed based on the Socio-demographic Index (SDI). Frontier analysis was used to visually demonstrate the burden of development levels in various regions, and the trends of migraine incidence, prevalence, and DALYs over the next decade were predicted.ResultsIn 2021, the global number of prevalent cases, incident cases, and DALYs for migraine were 1.158 billion, 90.18 million, and 43.38 million, compared with 1990, the percentage changes were 58, 42, and 58%, respectively. In 2021, the age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), and age-standardized DALY rate (ASDR) of migraine were the highest in areas with high SDI. Its prevalence, incidence, and DALYs were 15365.1, 1222.5, and 573.6 per 100,000 people. From 1990 to 2021, the ASDR showed an upward trend globally and in all regions, among which ASIR and ASPR in global, China, East Asia, high, high-middle SDI regions were on the rise, while they showed a downward trend in low, low-middle SDI regions. Frontier analysis showed that areas with high SDI generally had greater potential for improvement. We used a predictive model to estimate that ASIR, ASPR, and ASDR of migraine were all on the rise.ConclusionFrom 1990 to 2021, the global burden of migraine has increased significantly, especially in middle SDI region. This study highlights the importance of tailored interventions aimed at addressing migraine and thus contributing to the achievement of the Sustainable Development Goals set by the World Health Organization.